2017
DOI: 10.1021/acsmedchemlett.7b00117
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Paclitaxel to Hybrid Peptide Carrier and Biological Evaluation in Jurkat and A549 Cancer Cell Lines

Abstract: Paclitaxel (PTX) is one of the most potent cancer drugs; however, its low solubility and strong systemic side effects limit its clinical applications. To overcome these issues, new drug formulations and chemical modifications have been proposed. In this study, we present conjugation of PTX to hybrid collagen-cell penetrating peptide (COL-CPP) carriers. The peptide carrier is highly soluble and utilizes a unique stabilization strategy: folding into a triple helix. Here, we report the formation of PTX-COL-CPP pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Collagen can also act as a drug carrier or a drug targeted site. Hybrid collagen-cell penetrating peptide carriers improved resistance to enzymatic degradation [223]. Treating cancer with the single-chain fragment of cetuximab along with its collagen-binding domain demonstrated effective results [224].…”
Section: Effects Of Inhibitors Targeted Sites Of Inhibitors Typical Imentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen can also act as a drug carrier or a drug targeted site. Hybrid collagen-cell penetrating peptide carriers improved resistance to enzymatic degradation [223]. Treating cancer with the single-chain fragment of cetuximab along with its collagen-binding domain demonstrated effective results [224].…”
Section: Effects Of Inhibitors Targeted Sites Of Inhibitors Typical Imentioning
confidence: 99%
“…Collagen affinity can also be used to mediate targeted immunotherapy antibodies. Fusion of the collagen-binding protein lumican and cytokines increased the efficacy of systemic immunotherapies in a melanoma model [223]. The therapeutic use of immune checkpoint inhibitors and interleukin-2 by conjugation (for antibodies) or recombinant fusion (for cytokine) to the von Willebrand factor A3 domain (a collagen-binding domain) eradicated tumors and exhibited obvious safety and efficacy in a breast cancer model [225].…”
Section: Effects Of Inhibitors Targeted Sites Of Inhibitors Typical Imentioning
confidence: 99%
“…Cell-penetrating peptides (CPPs) have been successfully used as vectors for efficient transportation of low bioavailable drugs into cells. 16 CPPs are a class of small peptides with a few to 30 amino acids that show membrane translocation activities. Because of their intrinsic ability to gain access to cell interiors, they have been successfully used for intracellular delivery of various membrane-impermeable bioactive agents.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that many of these challenges can be resolved by introducing architectural motifs via synthetic linking of CPP with a collagen peptide 15,16 . This resulted in the formation of a triple helical nanocarrier that effectively delivered Paclitaxel to malignant cells 17 .…”
Section: Introductionmentioning
confidence: 99%